[La diagnosi psicopatologica nel lavoro psicologico-psichiatrico] - Roberto Infrasca (Clinical Management Issues, 2022)
The psychopathological diagnosis, which is crucial in the psychological-psychiatric work, is performed through tests and interviews aimed at evaluating the cognitive processes and the patients’ behavior. Feeling-thinking-communicating-acting process is particularly important, as it characterizes patients’ evolutionary phases and allows to move closer to the diagnosis. In this study, three patients with different psychological-psychiatric pathologies are described. For each case, verbal and non-verbal communication and psycho-emotional and cognitive sequence are analyzed. After this description, psychodiagnostic test results are discussed in order to highlight signs and symptoms of considered subjects. The described method allows to “explore” psychodynamic spaces hidden by psychic defenses that prevent a clear understanding of the psychic functioning and the operative plot at the intra- and inter-personal level of the subject.